The intentional thread : a guide to drawing, gesture, and color in stitch - Brandeis, Susan (Atglen, PA : Schiffer Publishing, 2019)
"Communicate your ideas using line, shape, color, and texture with this reference and how-to exploration in one. Whether your particular interest is pictorial, portraiture, abstract compositions, or actual text, you can 'say' almost anything with thread. More than 350 color photographs translate the techniques of drawing, painting, and good composition into the world of stitch, and 'Try This!' projects inspire your own individual approaches. Including the role of machine stitching, this design resource, learning tool, and inspirational reference helps practitioners at all levels, whether beginning student, dedicated amateur, or professional. Take a lyrical--but logical--journey of skill building, and begin to stitch intentionally and express your creative vision."--Page [4] of cover.
The elements of line. Line weight ; Line direction ; "Natural" mark-making: everybody does it ; Handwriting as drawing ; Large-scale gestures ; Feathered strokes and delicate lines ; Lines on "see-through" materials ; Contours and outlines -- Shapes and spaces : fills and shading. Thinking about color ; Fills : transparent ; Fills : opaque ; Fills : shaded ; Fills : textured -- Appendix 1. Getting started : a guide to stitching -- Appendix 2. Getting started : help from samplers -- Appendix 3. Getting started : matching expression and technique.
Includes bibliographical references (pages 217-219) and index.
Keywords: Drawing -- Technique; Embroidery -- Technique; Needlework -- Technique